2018
DOI: 10.3390/molecules23020360
|View full text |Cite
|
Sign up to set email alerts
|

Chemoselective Polymerization of Polar Divinyl Monomers with Rare-Earth/Phosphine Lewis Pairs

Abstract: This work reports the chemoselective polymerization of polar divinyl monomers, including allyl methacrylate (AMA), vinyl methacrylate (VMA), and 4-vinylbenzyl methacrylate (VBMA), by using simple Lewis pairs comprised of homoleptic rare-earth (RE) aryloxide complexes RE(OAr)3 (RE = Sc (1), Y (2), Sm (3), La (4), Ar = 2,6-tBu2C6H3) and phosphines PR3 (R = Ph, Cy, Et, Me). Catalytic activities of polymerizations relied heavily upon the cooperation of Lewis acid and Lewis base components. The produced polymers we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…Mechanistic investigations revealed that the LPP was initiated by the ninemembered addition intermediate resulting from the intramolecular 1,4-addition of rare-earth metal complexes to the monomer. Later in 2018, they reported the polymerization of conjugated polar alkenes, such as MMA, t BuMA, DMAA, and FMA as well as divinyl monomers AMA, VMA, and VBMA, by LPs consisting of homoleptic rare-earth aryloxides (Ln = Sc, Y, Sm, and La) as the LA and phosphines or NHCs as the LBs [73,74]. Among the investigated monomers, polymerization of MMA was relatively controlled over the M n and MWD in spite of low I*.…”
Section: Rare-earth Metal-or Si-based Lpsmentioning
confidence: 99%
“…Mechanistic investigations revealed that the LPP was initiated by the ninemembered addition intermediate resulting from the intramolecular 1,4-addition of rare-earth metal complexes to the monomer. Later in 2018, they reported the polymerization of conjugated polar alkenes, such as MMA, t BuMA, DMAA, and FMA as well as divinyl monomers AMA, VMA, and VBMA, by LPs consisting of homoleptic rare-earth aryloxides (Ln = Sc, Y, Sm, and La) as the LA and phosphines or NHCs as the LBs [73,74]. Among the investigated monomers, polymerization of MMA was relatively controlled over the M n and MWD in spite of low I*.…”
Section: Rare-earth Metal-or Si-based Lpsmentioning
confidence: 99%
“…[10,[14][15][16][17][18][19] So far, to retain the allyl group of AMA for further reactions, harsh conditions such as low temperature and/ or additional additives are usually required during polymerization. [7,11,20] Vapor deposition offers a more advantageous approach in synthesizing crosslinked films than traditional liquidbased methods, since polymerization and crosslinking take place during film formation as opposed to liquid-based film fabrication. Vapor-based approaches could also compensate for the shortcomings caused by the use of organic solvents, such as insoluble reactants, residual contaminants from solvent, and damage to substrates.…”
Section: Doi: 101002/macp201900299mentioning
confidence: 99%
“…However, radical polymerization of AMA under normal conditions may lead to crosslinking or cyclization of the side chain, depleting allyl groups at an early stage of polymerization (Figure c) . So far, to retain the allyl group of AMA for further reactions, harsh conditions such as low temperature and/or additional additives are usually required during polymerization …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the studies on the controlled or chemoselective addition polymerizations of conjugated polar alkene monomers represent four articles in this Special Issue [ 5 , 6 , 7 , 8 ]. Specifically, the controlled and efficient polymerizations of polar monomers such as methyl methacrylate (MMA), n -butyl methacrylate ( n BMA), and γ -methyl- α -methylene- γ -butyrolactone ( γ MMBL) catalyzed by the sterically hindered aryloxide-substituted alkylaluminum/ N -heterocyclic carbene (NHC) Lewis acid/base catalyst system were reported by Hong and co-workers [ 5 ].…”
mentioning
confidence: 99%